CHARACTERISTICS OF ABORTION SEEKING WOMEN: A STUDY OF FAISALABAD CITY - Muhammad Abdullah Avais; Nagina Parveen; Aijaz Ali Wassan et al. (Journal of University Medical & Dental College, 2016)
ABSTRACT INTRODUCTION: Abortion is a dead secret of every society. In Pakistan, due to multiple reasons women may pressurize to undergo induced abortion. They face socio-psychological, religious and cultural pressures. Meanwhile, extra/premarital relations and failure to adopt safe intercourse leads to un-wanted pregnancy and abortion is last hope in such conditions. OBJECTIVES: To ﬁnd out socio-economic background and reasons behind decision of induced abortion. PLACE: Study was conducted in Faisalabad city in August 2015. ETHICAL RULES: Due to sensitivity of issue identiﬁcation of respondents was not taken. MATERIAL AND METHODS: 12 clinics participated in this study voluntarily. Therefore, 67 women visited the clinics during study period for abortion were interviewed through convenience sampling technique. RESULTS: The results indicate that 31% respondents were belonging to age group 31-35 years, 55% respondents have matriculation or above education, 15% respondents aborted due to medical problems, 7% due to premarital relations and 30% terminated due to large number of children. Meanwhile, it was revealed that 52% respondents were house wives and 63% respondents have per month family income between11,000 to 15,000 Pakistani rupees. Moreover, it was conﬁrmed that 51% respondents had 3 to 4 children and 39% respondents adopted condom method to prevent pregnancy but in vain. Analysis of acquired data also conﬁrmed that 70% respondents did not know the side effects of induced abortion. CONCLUSION: Multiple factors like poverty, too many children, pre or extra marital relations, contraceptive failure and gander choice may lead to induced abortion or push the women to terminate pregnancy. Mostly abortion seeker women belong to middle class families who had low monthly family income. SUGGESTIONS: Prevention from unwanted pregnancies is best strategy to away from induced abortion.